Students' Cognitive Processes in Understanding Fractions Through the Tourist Context - Sukasno; Zulkardi; Putri, Ratu Ilma Indra; Somakim (Mathematics Education Journal, 2024)
This research aims to describe students' cognitive processes in understanding fractions through a tourist context. This research method is design research. The data collection technique is through tests and in-depth interviews. The results of this research show that student's cognitive process in understanding fractions through a tourism context is that students first understand the problems in the tourism context of Lake Air Gegas; then students create mathematical models based on context; third, students complete mathematical models based on context; the fourth student creates a solution to the context problem; Finally, students make mathematical conclusions. Through the tourism context, students can solve problems appropriately. The conclusion is that there are five stages of students' cognitive process in discovering the principle of multiplication of fractions, namely students understand the problem through a tourism context, create a mathematical model based on context, complete a mathematical model based on context, create a context problem solution, and end by making mathematical conclusions about the principle of Multiplication of Fractions. Therefore, it is recommended that mathematics teachers use the tourism context as a starting point for mathematics learning.